DNA methylation landscapes before and after Pacific Oyster Mortality Syndrome are different within and between resistant and susceptible Magallana gigas - Valdivieso Munoz, Alejandro; Morga, Benjamin; Dégremont, Lionel; Mege, Mickael; Dorant, Yann; Escoubas, Jean Michel; Gawra, Janan; De Lorgeril, Julien; Mitta, Guillaume; Cosseau, Céline; Vidal Dupiol, Jeremie (Science of The Total Environment, 2025)
Pacific oysters face recurring outbreaks of Pacific Oyster Mortality Syndrome (POMS), a polymicrobial multifactorial disease. Although this interaction is increasingly understood, the role of epigenetics (e.g., DNA methylation) appears to be of fundamental importance because of its ability to shape oyster resistance/susceptibility and respond to environmental triggers, including infections. In this context, we comprehensively characterized basal (no infection) and POMS-induced changes in the methylome of resistant and susceptible oysters, focusing on the gills and mantle. Our analysis identified differentially methylated regions (DMRs) that revealed distinct methylation patterns uniquely associated with the susceptible or resistant phenotypes in each tissue. Enrichment analysis of genes bearing DMRs highlighted that these epigenetic changes were specifically linked to immunity, signaling, metabolism, and transport. Notably, 31 genes with well-known immune functions were differentially methylated after POMS, with contrasting methylation patterns between the phenotypes. Based on the methylome differences between phenotypes, we identified a set of candidate epibiomarkers that could characterize whether an oyster is resistant or susceptible (1998 candidates) and whether a site has been exposed to POMS (164 candidates). Overall, the findings provide a deeper understanding of the molecular interactions between oysters and POMS infection, opening new questions about the broader implications of epigenetic mechanisms in host-pathogen dynamics and offering promising strategies for mitigating the impacts of this devastating disease. Beyond its biological aspects, this study provides insights into potential epigenetic biomarkers for POMS disease management and targets for enhancing oyster health and productivity.